Implementasi Model Pembelajaran Student Teams Achievement Division dan Team Assisted Individualization ditinjau dari Kemampuan Spasial Siswa - Kusuma, Arie Purwa (Al-Jabar: Jurnal Pendidikan Matematika, 2017)
The objectives of this research were to investigate the effect of the learning models on the learning achievement in Mathematics viewed from the spatial ability of the students. This research used the quasi experimental research method with the factorial design of 3 x 3. The samples of the research were taken by using the cluster random sampling technique. The data of the research were analyzed by using the two-way analysis of variance with unbalanced cells.The results of the research are as follows.1) The cooperative learning model of the STAD type results in a better learning achievement in Mathematics than the cooperative learning model of the TAI type and the direct learning model, and the cooperative learning model of the STAD type results in a better learning achievement in Mathematics than the conventional learning model.2) The learning achievement in Mathematics of the students with the high spatial ability was better than that of the students with the moderate and low spatial abilities, and the learning achievement in Mathematics of the students with the moderate spatial ability was better than that of the students with the low spatial ability. 3) There was an interaction the aforementioned learning models and the categories of the spatial ability on the learning achievement in Mathematics of the students.